Private international law in Nigeria - Okoli, Chukwuma Samuel Adesina; Oppong, Richard Frimpong, 1978- (Oxford ; Hart, 2020)
"This book examines the rules, principles, and doctrines in Nigerian law for resolving cases involving cross-border issues. It is the first book-length treatise devoted to the full spectrum of private international law issues in Nigeria. As a result of increased international business transactions, trade, and investment with Nigeria, such cross-border issues are more prevalent than ever. The book provides an overview of the relevant body of Nigerian law, with comparative perspectives from other legal systems. Drawing on over five hundred Nigerian cases, relevant statutes, and academic commentaries, this book examines jurisdiction in interstate and international disputes, choice of law, the enforcement of foreign judgments and international arbitral awards, domestic remedies affecting foreign proceedings, and international judicial assistance in the service of legal processes and taking of evidence. Academics, researchers, and students, as well as judges, arbitrators, practitioners, and legislators alike will find Private International Law in Nigeria an instructive and practical guide"--
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Conflict of laws -- Nigeria; Private international law & conflict of laws; Electronic books